2022
DOI: 10.1002/ijc.34288
|View full text |Cite
|
Sign up to set email alerts
|

Out of the cycle: Impact of cell cycle aberrations on cancer metabolism and metastasis

Abstract: The use of cell cycle inhibitors has necessitated a better understanding of the cell cycle in tumor biology to optimize the therapeutic approach. Cell cycle aberrations are common in cancers, and it is increasingly acknowledged that these aberrations exert oncogenic effects beyond the cell cycle. Multiple facets such as cancer metabolism, immunity and metastasis are also affected, all of which are beyond the effect of cell proliferation alone. This review comprehensively summarized the important recent finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 216 publications
0
8
0
Order By: Relevance
“…Our study also found that miR-4477b inhibited gluconeogenesis by restricting TEF and FBP1, while TEF promoted gluconeogenesis by transcriptionally regulating PCK1 and PCK2. TEF was previously reported to retard bladder cancer cell growth by inhibiting G1/S transition and regulating AKT/FOXOs signaling, which are both closely related to glycolysis/gluconeogenesis homeostasis [ 43 45 ]. Interestingly, our research did not identify any other miRNAs previously reported to regulate gluconeogenesis under various conditions (miR-158-5p, miR-351, miR-451, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…Our study also found that miR-4477b inhibited gluconeogenesis by restricting TEF and FBP1, while TEF promoted gluconeogenesis by transcriptionally regulating PCK1 and PCK2. TEF was previously reported to retard bladder cancer cell growth by inhibiting G1/S transition and regulating AKT/FOXOs signaling, which are both closely related to glycolysis/gluconeogenesis homeostasis [ 43 45 ]. Interestingly, our research did not identify any other miRNAs previously reported to regulate gluconeogenesis under various conditions (miR-158-5p, miR-351, miR-451, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…Our study demonstrated that the KLF5-MLK4-PCK1 axis exerts an oncogenic function in lung carcinogenesis with altered glucose metabolism. These findings are interesting in that we unraveled the unusual link between a kinase chiefly involved in the cell cycle progression and a metabolic enzyme [ 24 ]. Moreover, we showed that MLK4 and PCK1 are oncogenic factors in lung cancer with potential clinical and prognostic significance.…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrated that PCK1 expression could be high in a significant subset of patients using immunohistochemistry on tissue microarray, that it was significantly correlated with a worse prognosis, and that it was regulated by MLK4 and CREB in low glucose media conditions. Meanwhile, CREB was well-known to regulate the transcription of PCK1, at least in gluconeogenic tissues [ 24 , 28 ]. By siRNA-mediated CREB inhibition and selective pharmacologic inhibitor of CREB, we demonstrated that this regulation of PCK1 by CREB was also present in lung adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…An increase in the degree of glycolysis in tumors occurs to meet the energy demands of rapidly proliferating tumor cells, and glycolysis can also produce intermediate metabolites supporting the biosynthesis of nucleotides, amino acids, and lipids, thus allowing the rapid proliferation of tumor cells ( Feng et al, 2020 ). Glucose metabolism is coupled to cell cycle progression, and glucose metabolism ensures adequate ATP and synthetic metabolites at different stages of the cell cycle ( Cheung et al, 2022 ). 6-Phosphofructo-2-kinase (PFKFB3) can promote cell cycle progression through CDK1-mediated phosphorylation of P27 ( Yalcin et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%